HISTORICAL PROCESSES OF BORROWING FOREIGN WORDS INTO ENGLISH - Ruziev Khusniddin Bakhritdinovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores the historical borrowing of foreign words into English from Latin, French, Greek, and other languages. It highlights key periods and influences, including colonization and globalization. Examples from science, law, and culture illustrate these borrowings. The study shows how English has continually expanded its vocabulary through contact with other languages.